IMPACT OF NATIONAL CULTURE ON EARNINGS MANAGEMENT: A COMPARATIVE STUDY OF EUROPE AND ASIA - DANGAYACH, HARSH (2017)
The present research examines the effect of national culture on the earnings management in both Europe and Asia and make a comparative study. The global perspective on earnings management reveals the differences in earnings management in different nations. The earnings management has several forms and it involves the system of carefully selecting the estimates of accounting and operating or investment decisions’ timing to move reported earnings downward or upward for the achievement of a specific goal. The national culture has an important role in creating a basis for a person’s culture. The study collected financial statements of highly traded financial organisations in the European and Asian nations wherein the sample collected data from 100 companies wherein ‘Discretional accruals’ is used as a proxy for Earnings Management. The findings of the research revealed the need for changes that exists based on the environment of each nation wherein the relationship between various dimensions and earnings management variable considered (Discretionary Accruals) was discerned. However, the present research is limited to examine the various dimensions of culture and how they are related with the earnings management variable (Discretionary Accruals) in the select European and Asian nations.